Analiza finansowa firmy na przykładzie Tar-Groch-Fil Sp.J. (lata 2012-2014) - Drożdż, Robert (My University, 2015)
Przedmiotem rozważań prezentowanej pracy jest przedstawienie analizy finansowej w jako narzędzia pozyskiwania wiedzy o przedsiębiorstwie. Celem badawczym jest „case-study” oceny kondycji finansowej wybranej firmy z sektora MSP. Rozdział pierwszy – teoretyczny – ma charakter wprowadzający. Jego celem jest ukazanie istoty analizy finansowej, jej zakresu badań, rodzajów oraz stosowanych metod i technik. Celem rozdziału drugiego jest klasyfikacja materiałów źródłowych, omówienie ich wartości poznawczej oraz cech jakościowych. W rozdziale trzecim dokonano prezentacji firmy Tar-Groch-Fil, uwzględniając jej historię, posiadane zasoby fizyczne i niematerialne. W rozdziale czwartym przeprowadzono analizę kondycji finansowej badanej spółki. Na podstawie sprawozdań finansowych za lata 2012-2014 dokonano analizy poziomej i pionowej bilansu oraz rachunku zysków i strat, a także dokonano syntetycznej oceny kondycji przedsiębiorstwa opartej na wybranych wskaźnikach finansowych.

The main concept of this thesis is to provide some exposure to financial analysis as a tool in acquiring and developing knowledge concerning the crucial characteristics of company’s profile. In the analyzing part of the thesis the “case-study” was chosen as the most accurate and appropriate method to establish the company’s financial value as one of the MSP’s companies sector. Chapter one is theoretical and introductory in approach. In deals with the main concepts and formulas of financial analysis, along with the other crucial information, such as the financial study area with some insights into the analytical techniques and methods .Chapter two helps identify and classify the sources, as well as, discuss their cognitive values and determine qualitative features .Chapter three provides an outline of the “Tar-Groch-Fil” company’s profile which starts with the history of its development and identifies all company’s physical and non-material assets. Chapter four consists basic information about the company’s financial condition based on the financial reports which refer to the 2012-2014 period of time. This practical part is focused on financial analysis itself by using horizontal and vertical analysis, as well as, profit and loss statement account. Furthermore, it covers the synthetic company’s evaluation and financial condition assessment on the basis of some financial ratios.
Company's Financial Analysis on the basis of Tar-Groch-Fil - General Partnership Company (2012-2014 period of time)
Keywords: analiza finansowa; Tar-Groch-Fil; kondycja finansowa przedsiębiorstwa; wskaźniki finansowe; lata 2012-2014; financial analysis; condition assessment company; financial ratios; 2012-2014 period of time